EXPLOITATION OF RESIDENTIAL BUILDINGS IN WINTER SEASON (American Journal of Technology and Applied Sciences, 2023)
In preparing the building for the winter season, heating measures that ensure efficient use of heat, as well as measures that envisage the efficient use of hot and cold water and electricity are of great importance.